Rankprop: a web server for protein remote homology detection - Melvin, Iain (Oxford University Press, 2009)
Summary: We present a large-scale implementation of the Rankprop protein homology ranking algorithm in the form of an openly accessible web server. We use the NRDB40 PSI-BLAST all-versus-all protein similarity network of 1.1 million proteins to construct the graph for the Rankprop algorithm, whereas previously, results were only reported for a database of 108 000 proteins. We also describe two algorithmic improvements to the original algorithm, including propagation from multiple homologs of the query and better normalization of ranking scores, that lead to higher accuracy and to scores with a probabilistic interpretation. Availability: The Rankprop web server and source code are available at http://rankprop.gs.washington.edu Contact: iain@nec-labs.com; noble@gs.washington.edu